2015
DOI: 10.1590/0103-9016-2013-0429
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory quotient: innovative method for monitoring ‘Royal Gala’ apple storage in a dynamic controlled atmosphere

Abstract: Apples (Malus domestica, Borkh.) which are not stored at low temperature or in a properly controlled atmosphere (CA) may have a high metabolic rate during the postharvest stage resulting in losses in quality. The aim of this study was to evaluate the quality of 'Royal Gala' apple fruit stored in accordance with a new method of dynamic controlled atmosphere (DCA).The respiratory quotient (RQ) was monitored at two temperatures which were then compared using a commercially available technology based on chlorophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…The large errors found offer a plausible explanation for the highly pressure dependent RQ estimates discussed in our previous work (Bessemans et al, 2016). Also, they explain the high variation in RQ measurements reported in other recent research in the field, where the RQ of stored fruit was estimated based on measured changes in gas partial pressure of O2 and CO2 over a time period of 24 h and leakage of the cool room was not taken into account (Brackmann, 2015;Weber et al, 2015;Both et al, 2017).…”
Section: Leakage Correction Improves Estimate Of Rqmentioning
confidence: 50%
“…The large errors found offer a plausible explanation for the highly pressure dependent RQ estimates discussed in our previous work (Bessemans et al, 2016). Also, they explain the high variation in RQ measurements reported in other recent research in the field, where the RQ of stored fruit was estimated based on measured changes in gas partial pressure of O2 and CO2 over a time period of 24 h and leakage of the cool room was not taken into account (Brackmann, 2015;Weber et al, 2015;Both et al, 2017).…”
Section: Leakage Correction Improves Estimate Of Rqmentioning
confidence: 50%
“…Mealiness is one important physiological disorder for apples of the 'Gala' group, which is described by a farinaceous texture and loss of juiciness due to the middle lamella degradation and subsequent cell separation (Prasanna et al 2007;Payasi et al 2009), decreasing apple quality and possibly making it unsuited for commercialization (Weber et al 2015). In this research, fruit of the control, NAA and NAA plus Ethephon treatments showed the highest mealiness occurrence (Fig.…”
Section: Postharvest Quality Of 'Brookfield' Applementioning
confidence: 61%
“…The very low oxygen content (ULO) commonly used for long-term storage of apples cannot be used for pears due to their greater susceptibility to damage due to oxygen deficiency [17]. Low oxygen levels trigger anaerobic respiration resulting in the accumulation of alcohol in pears, which is directly responsible for damage to the flesh [18]. This can be prevented by the monitoring of changes in the alcoholic respiration in the atmosphere [19].…”
Section: Introductionmentioning
confidence: 99%